KIBRA: a new gateway to learning and memory? - Schneider, Armin; Huentelman, Matthew J.; Kremerskothen, Joachim; Duning, Kerstin; Spoelgen, Robert; Nikolich, Karoly (Frontiers in Aging Neuroscience, 2010)
The genetic locus encoding KIBRA, a member of the WWC family of proteins, has recently been shown to be associated with human memory performance through genome-wide single nucleotide polymorphism screening. Gene expression analysis and a variety of functional studies have further indicated that such a role is biologically plausible for KIBRA. Here, we review the existing literature, illustrate connections between the different lines of evidence, and derive models based on KIBRA’s function(s) in the brain that can be further tested experimentally.